Notes on normal distribution - Wilkowski, Andrzej (Uwagi o rozkładzie normalnym, 2009)
In this paper several characteristics of normal distribution are presented. A new bimodal Weber distribution model is also postulated
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 71-78
Keywords: normal distribution; Cramer‟s theorem; Feller's and Novak's characterizations; Webber‟s distribution